Catheter strategy to ease the procedure and reduce radiation exposure when requiring neck access. Issue 1 (28th June 2020) - Kubicki, Rouven; Hummel, Johanna; Höhn, René; Müller, Kevin; Stiller, Brigitte; Grohmann, Jochen
Abstract : Objectives: To assess the potential occupational radiation reduction and technical feasibility in patients rotated 180° (upside-down) when requiring neck access for transcervical or trans-subclavian catheterisation. Methods: Upside-down positioning is defined as rotating patients in supine position by 180°, so that the feet come to rest where the head would otherwise be. We retrospectively evaluated all these procedures performed between March 2016 and May 2019. Furthermore, two different phantoms (paediatric and adult) were used prospectively to quantify the occupational dose between conventional or upside-down positioning. In this context, ambient dose equivalents were measured using real-time dosimeters. Three different projection angles were applied. Results: 44 patients with median age and body weight of 1.0 year (range 0–56) and 9.5 kg (range 1.3–74.3) underwent 63 procedures positioned upside-down. This position proved advantageous for practical reasons, since the length of the examination table could be optimally used. Additionally, it resulted in a significantly lower overall ambient dose equivalent for the primary operator (PO) of 94.8% (mean: 2569±807 vs 135±23 nSv; p<0.01) in the adult, and of 65.5% (mean: 351±104 vs 121±56 nSv; p<0.01) in the paediatric phantom, respectively. Conclusion: Upside-down positioning facilitates handling in a straightforward manner when access from the neck is required. Moreover, it significantly reduces local radiation exposure for the PO in the paediatric and, most impressively, in the adult phantom.